POTENSI GANGGUAN KETENTERAMAN DAN KETERTIBAN UMUM DI PEMILIHAN KEPALA DESA DAN PEMILIHAN KEPALA DAERAH (PERNAK PERNIK PEMILIHAN LANGSUNG) - Dedy Suhendi (Fakultas Hukum Tata Pemerintahan, 2020)
Village head elections (pilkades) are political activities / events that show how the process (party) of democracy is at the village level. Pilkades is not merely a transfer of leadership for the sustainability of government and development in the village, or how a power struggle with a campaign strategy is carried out in order to get sympathy and support from the village community, but more than that it concerns prestige / dignity and honor so that it often creates tough competition and conflict. Since the enactment of Law no. 23 of 2004 and now Law no. 32 of 2014 concerning Regional Government, regional heads are directly elected by the people. This study aims to explain the possible potential for disturbances of peace and public order that can occur during the pre-post-regional head elections such as village head elections which result in disturbances of peace and public order, then try to analyze and study and anticipate as an effort to minimize possible disturbances. The method used in this research is descriptive research method by emphasizing the researcher's efforts to describe the phenomenon based on the experiences of research participants while on duty in the region and supplemented with the results of observations. The final results of this study are expected to be able to provide recommendations and solutions to a more appropriate “pilkada” model. The conclusion of this research is in order to enforce peace and public order in the regions by preventing disturbances of peace and order from pre to post Pilkada.